1996
DOI: 10.1099/0022-1317-77-8-1893
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of C-terminal deletion mutants of Epstein--Barr virus thymidine kinase

Abstract: Thymidine kinase fiR) activity was detected following expression of the TK gene of Epstein-Barr virus (EBV) using the pET expression plasmid and E. coli BL21(DE3)pLysS. To study the amino acid residues required at the C terminus of the EBV TK protein for enzymatic activity, a series of C-terminal deletion mutants was generated by direct truncation, linker insertion or PCR mutagenesis to create stop codons at particular sites. Deletion of nine residues from the C terminus caused a 35% reduction in TK activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In this sense, the reduced activity of the Δ8 mutant relative to the other C-terminal deletion mutants (Table 3) is unanticipated. However, we note that similar effects have been reported by others who carried out C-terminal deletion studies, including the IN269 mutation for the integrase of HIV [104], the Δ8 and Δ9 mutants of the thymidine kinase of Epstein-Barr virus [105], and the D5 and D10 mutants of the plant vacullar H (+)-pyrophosphatase [106]. Differential proteolysis may also explain why the Δ8 construct does not follow the same trend as the other mutants.…”
Section: Discussionsupporting
confidence: 83%
“…In this sense, the reduced activity of the Δ8 mutant relative to the other C-terminal deletion mutants (Table 3) is unanticipated. However, we note that similar effects have been reported by others who carried out C-terminal deletion studies, including the IN269 mutation for the integrase of HIV [104], the Δ8 and Δ9 mutants of the thymidine kinase of Epstein-Barr virus [105], and the D5 and D10 mutants of the plant vacullar H (+)-pyrophosphatase [106]. Differential proteolysis may also explain why the Δ8 construct does not follow the same trend as the other mutants.…”
Section: Discussionsupporting
confidence: 83%
“…This hypothesis is very unlikely. Indeed, several studies of herpesviruses and poxviruses have demonstrated previously that the C-terminal region of TK is essential for its activity (23). For example, it has been demonstrated previously that the last 10 residues of the 607-aa-long Epstein-Barr virus TK are essential for its activity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies of herpesviruses and poxviruses have demonstrated previously that the C-terminal region of TK is essential for its activity (23). For example, it has been demonstrated previously that the last 10 residues of the 607-aa-long Epstein-Barr virus TK are essential for its activity (23). In comparison to EpsteinBarr virus TK, KHV TK is rather small, consisting of only 217 aa, among which only the first 185 residues are expressed by the FL BAC-excised strain.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant plasmids obtained were used to transform the Escherichia coli strain BL21(DE3)pLysS [29]. One colony was …”
Section: Expression Of the Tk Proteinmentioning
confidence: 99%
“…However, the structurefunction relationship of EBV TK has been addressed rarely. In our previous study, we have shown that the C-terminus of EBV TK is important for its activity [29]. In the present study, we sought to identify and characterize the nucleoside-binding sites of the enzyme.…”
Section: Introductionmentioning
confidence: 99%